ENGLISH EDUCATION FOR ISLAMIC UNIVERSITY IN INDONESIA: STATUS AND CHALLENGE - M. Noor Sulaiman Syah (P3M STAIN Kudus, 2015)
Education is the foundation of Islam, knowledge acquisition is one of the sublime spiritual merits of the learned over the ignorant. Education prepares an individual to adjust well in the society and to develop a high sense of responsibility to self and to the society. It enables a person to think critically and constructively. English is one of the language being taught in Indonesia. It is become a main foreign language which take an important role for education in Indonesia. English education can be accepted in Indonesia by means of some challenges. And recently it gain an important status in Islamic university in Indonesia. It could cover the modernization and islamization goals in Islamic university in Indonesia.